Floquet engineering of excitons in two-dimensional halide perovskites via biexciton states - Cai, Rui (2024)
Layered two-dimensional halide perovskites (2DHPs) exhibit exciting non-equilibrium properties that allow the manipulation of energy levels through coherent light-matter interactions. Under the Floquet picture, novel quantum states manifest through the optical Stark effect (OSE) following intense subresonant photoexcitation. Nevertheless, a detailed understanding of the influence of strong many-body interactions between excitons on the OSE in 2DHPs remains unclear. Herein, we uncover the crucial role of biexcitons in photon-dressed states and demonstrate precise optical control of the excitonic states via the biexcitonic OSE in 2DHPs. With fine step tuning of the driven energy, we fully parametrize the evolution of exciton resonance modulation. The biexcitonic OSE enables Floquet engineering of the exciton resonance with either a blue-shift or a red-shift of the energy levels. Our findings shed new light on the intricate nature of coherent light-matter interactions in 2DHPs and extend the degree of freedom for ultrafast coherent optical control over excitonic states.